Modeling concept and analytical dependency between data and goal: A case of Australian Airlines - Tengku Adil Tengku Izhar; Torab Torabi; Muhammad Ishaq Bhatti (The International Journal of Management Science and Information Technology (IJMSIT), 2017)
This paper proposes an approach to utilise information from operational data to support the organization goal. The challenge in this issue is how to convert this vast of data into useful information. This is critical for all enterprises to remain competitive. In this paper, we emphasizes the dependency relationship involve between the elements such as organization goal, sub-goal, action and data. This relationship is important to assist the development of data measurement, data analysis and data modeling.
Keywords: 650; Action; Data; Goals; Organization; Task